Studies On The Effect Of Addition Modified Sago Starch On Mechanical Properties Of Natural Rubber And Synthetic Polyisoprene Latex Films - So’od, Nurul Fazliniza (Universiti Sains Malaysia, 2018)
This research is formulated to study the effect of addition of modified sago starch (dextrine) on the mechanical properties of natural rubber (NR) and synthetic polyisoprene (PI) latex films. This works involved comparison of different loading of modified sago starch at 10,20 and 30 phr in NR and PI latex compounds. The effect of post processing parameters in NR and PI latex films was also investigated. The leaching process using tap water was carried out for 30 minutes at room temperature and accelerated aging process was carried out at 100°C for 3 days. Modified sago starch was prepared in the aired oven for 8 hours at 150°C prior to dispersion of modified sago starch. Then latex compounding was carried out into flat-bottomed flask at 70°C. After compounding, dipping and drying processs were conducted to produce latex films. The mechanical properties( tensile properties and tear strength) were carried out to all the films by using Instron machine. Based on the results obtained, 10 phr loading of modified sago starch showed increased in tensile strength and elongation at break for NR while elongation at break for PI latex films. For post processing, leaching process has improved the mechanical properties of PI latex films due to removal of unreacted rubber compounding ingredients in the PI latex. Ageing resulted in decreased of mechanical properties of PI latex films due to breakage of sulphur crosslinks that exposed in high temperature.